Penerapan Metode Design Thinking Pada Perancangan UI/UX Pada Aplikasi Penyewaan Motor untuk Pariwisata - Antika, Rindi; Nainggolan, RIbka Chrystin Lawrencia; Priambodo, Rizki Ardhan; Inayatullah, Inayatullah (Universitas Multi Data Palembang, 2024)
This study delves into the application of Design Thinking in designing the user interface (UI/UX) for a touring motorbike rental app, primarily focusing on user experience and accessibility. Involving various stages, from empathizing with users, defining design goals, ideation, and prototyping, to application testing, the questionnaire results indicate that most respondents (85.7%) know about this app. Furthermore, 57.1% perceive its benefits, and 71.4% choose to use the app. Although only 28.6% are familiar with the app, the average ratings for registration & login, navigation menu, and product & transaction details are 5.14/7, 5.57/7, and 4.86/7. This research significantly contributes to optimizing the touring motorbike rental app through the Design Thinking approach.This study delves into the application of Design Thinking in designing the user interface (UI/UX) for a touring motorbike rental app, primarily focusing on user experience and accessibility. Involving various stages, from empathizing with users, defining design goals, ideation, and prototyping, to application testing, the questionnaire results indicate that most respondents (85.7%) know about this app. Furthermore, 57.1% perceive its benefits, and 71.4% choose to use the app. Although only 28.6% are familiar with the app, the average ratings for registration & login, navigation menu, and product & transaction details are 5.14/7, 5.57/7, and 4.86/7. This research significantly contributes to optimizing the touring motorbike rental app through the Design Thinking approach.